Proteomic analysis of three medically important Nigerian Naja (Naja haje, Naja katiensis and Naja nigricollis) snake venoms. (15th July 2021) - Adamude, Fatima Amin; Dingwoke, Emeka John; Abubakar, Mujitaba Suleiman; Ibrahim, Sani; Mohamed, Gadija; Klein, Ashwil; Sallau, Abdullahi Balarabe
Abstract: Proteomics technologies enable a comprehensive study of complex proteins and their functions. The venom proteomes of three medically important Nigerian Elapidae snakes Naja haje, Naja katiensis and Naja nigricollis was studied using HILIC coupled with LC-MS/MS analysis. Results revealed a total of 57, 55, and 46 proteins in the venoms of N. haje, N. katiensis, and N. nigricollis, respectively, with molecular mass ranging between 5 and 185  kDa. These snakes have 38 common proteins in addition to 3 uncommon proteins: actiflagelin, cathelicidin, and cystatin identified in their venoms. The identified proteins belonged to 14 protein families in N. haje and N. katiensis, and 12 protein families in N. nigricollis . Of the total venom proteins, 3FTx was the most abundant protein family, constituting 52% in N. haje and N. katiensis, and 41% in N. nigricollis, followed by PLA2, constituting 37% in N. nigricollis, 26% in N. haje, and 24% in N. katiensis . Other protein families, including LAAO, CRISPs, VEGF, PLB, CVF, SVMP, SVH, AMP, PI, Globin, Actin, and C-type lectins, were also detected, although, at very low abundances. Quantification of the relative abundance of each protein revealed that alpha and beta fibrinogenase and PLA2, which constituted 18–26% of the total proteome, were the most abundant. The 3 uncommon proteins have no known function in snake venom. However, actiflagelin activates sperm motility; cystatin inhibits angiogenesis, while cathelicidin exerts antimicrobial effects. The three Nigerian Naja genus proteomes displayed 70% similarity in composition, which suggests the possibility of formulating antivenom that may cross-neutralise the venoms of cobra species found in Nigeria. These data provide insights into clinically relevant peptides/proteins present in the venoms of these snakes. Data are available via ProteomeXchange with identifier PXD024627. Highlights: Venom proteomics of three Nigerian elapidae snakes associated with envenoming are presented. 3FTx was the most abundant protein family, constituting 52% in Naja haje and Naja katiensis, and 41% in Naja nigricollis. These Naja genus proteomes displayed 70% similarity in composition, with clinically relevant proteins being identified.